Analysis of the Relationship between Energy Price Changes and Stock Market Indices in Developed Countries - Nakhipbekova, Symbat; Baibosynova, Gulzhan; Batyrova, Nazygul; Kulbayeva, Aigerim (International Journal of Energy Economics and Policy, 2020)
Oil is an important energy source and basic raw material in the manufacturing process. Therefore, the economies of every country in the world are directly or indirectly dependent on oil. The chain effect of the addiction in question also affects the financial markets. In the study, long-term relationship between energy prices (oil, natural gas and electricity prices) and stock market index for developed countries was analyzed with Multiple Structural Break Panel Cointegration Test. The causality relationship between the variables was examined with Dumitrescu-Hurlin Panel Causality Test. According to the findings of the analysis, it was determined that the series move together in the long term. However, while there was causality between oil prices and natural gas prices in the short term, it was revealed that there was no causality between electricity prices and stock market indices. Keywords: oil prices, natural gas, electricity, stock market index, panel data analysis JEL Classifications: C23, G15, Q40 DOI: https://doi.org/10.32479/ijeep.10048